The Influence of Experiential Marketing and Social Media on Customer Loyalty with Repurchase Intention as a Moderating Variable on the Lafiye Hijab Brand (Case Study of Students from the Faculty of Economics and Business, University of Bandar Lampung) - Amisa Fitri, Elysa; Andala Rama Putra Barusman (Eastasouth Institute, 2025)
This research explores how experiential marketing and social media marketing influence customer loyalty to the Lafiye Hijab brand, with repurchase intention examined as a moderating factor. A quantitative approach was employed utilizing the Structural Equation Modeling (SEM) method, with data collected from 280 randomly selected university students who actively engage in social media. A five-point Likert scale questionnaire served as the primary research instrument, while data analysis was conducted using SmartPLS software to evaluate the relationships between the variables. The results indicate that both experiential and social media marketing have a significant positive impact on customer loyalty. Additionally, repurchase intention strengthens this influence as a moderating variable, while brand trust plays a key mediating role by clarifying the interactions among the variables. These findings offer valuable strategic insights for hijab brands seeking to boost customer loyalty by creating more engaging and meaningful marketing campaigns, like crafting emotionally resonant content. This study makes a distinctive contribution by examining the interplay between experiential marketing, social media marketing, repurchase intention, and customer loyalty in the context of hijab brands in Indonesia, a subject that has received limited attention in previous studies.